Fatigue crack growth modelling and analysis - Wong, Brian Sixian (2018)
Material fatigue is a very common problem faced by most engineers that cannot be ignored. It can be addressed by using specialised software to analysis the crack growth rate and lifespan of the material. These software offer a wide range of tools which allow users to obtain their desired results. However, the use of these software can be very expensive to acquire. A cheaper alternative is to self-create a computer program to calculate the fatigue lifespan, using the simple Paris law. The objective of this project is to study and investigate the feasibility of writing a program to calculate the fatigue life of a material.